Watershed land use decreases the nitrogen limitation of benthic algal growth in coastal wetlands of a large oligotrophic lake - Cooper, Matthew J.; Wheeler, Michele C. (Frontiers in Freshwater Science, 2025)
IntroductionIdentifying patterns in the primary limiting nutrients of basal trophic levels such as benthic algae can inform the prediction of potential ecological responses to anthropogenic nutrient loading. In coastal wetlands of the Laurentian Great Lakes, reduced concentrations of reactive nitrogen species such as ammonium and nitrate may limit algal growth, especially when nutrient loading is minimal. However, the response of benthic algae to macronutrient inputs remains understudied, especially in Lake Superior coastal wetlands.MethodsWe conducted nutrient amendment assays using nutrient diffusing substrate devices in 25 coastal wetlands along the southwestern shore of Lake Superior in the spring, summer, and fall. These assays allowed us to investigate seasonal and regional variation in nutrient limitation status and the relationship between nutrient limitation, in situ water quality (dissolved and total nitrogen and phosphorus, water temperature, dissolved oxygen, specific conductivity, and total suspended solids), and watershed land use.ResultsWe found that nitrogen limitation was common, particularly during summer, with 60% of wetlands exhibiting this condition, while phosphorus limitation was not observed in any wetland during any season. The strongest N limitation was found in wetlands of the Apostle Islands National Lakeshore where watershed land cover was almost entirely natural. Wetlands with more developed watersheds, including those of the St. Louis River Estuary, had a lower degree of N limitation (p = 0.003). Nitrogen limitation was observed in spring, summer, and fall, but was most pronounced in the summer.DiscussionThese findings suggest that N limitation predominates in these Lake Superior coastal wetlands, contrasting with the well-documented phosphorus limitation of the lake's pelagic zone. Our study also highlights the potential for anthropogenic N loading to stimulate excessive benthic algal growth in Lake Superior coastal wetlands, particularly in more developed regions. These findings are consistent with those for coastal wetlands in other regions of the Great Lakes and support the need for continued monitoring and targeted mitigation of both nitrogen and phosphorus loading to shoreline habitats of large lakes.